Effect of novel short‐arm human centrifugation‐induced gravitational gradients upon cardiovascular responses, cerebral perfusion and g‐tolerance. (19th August 2020) - Laing, Charles; Green, David A.; Mulder, Edwin; Hinghofer‐Szalkay, Helmut; Blaber, Andrew P.; Rittweger, Joern; Goswami, Nandu
Abstract : Key points: The aim of this study was to determine the effect of rotational axis position (RAP and thus g‐gradient) during short‐arm human centrifugation (SAHC) upon cardiovascular responses, cerebral perfusion and g‐tolerance. In 10 male and 10 female participants, 10 min passive SAHC runs were performed with the RAP above the head (P1), at the apex of the head (P2), or at heart level (P3), with foot‐level Gz at 1.0 g, 1.7 g and 2.4 g . We hypothesized that movement of the RAP from above the head (the conventional position) towards the heart might reduce central hypovolaemia, limit cardiovascular responses, aid cerebral perfusion, and thus promote g‐tolerance. Moving the RAP footward towards the heart decreased the cerebral tissue saturation index, calf circumference and heart rate responses to SAHC, thereby promoting g‐tolerance. Our results also suggest that RAP, and thus g‐gradient, warrants further investigation as it may support use as a holistic spaceflight countermeasure. Abstract: Artificial gravity (AG) through short‐arm human centrifugation (SAHC) has been proposed as a holistic spaceflight countermeasure. Movement of the rotational axis position (RAP) from above the head towards the heart may reduce central hypovolaemia, aid cerebral perfusion, and thus promote g‐tolerance. This study determined the effect of RAP upon cardiovascular responses, peripheral blood displacement (i.e. central hypovolaemia), cerebral perfusion and g‐tolerance, and their inter‐relationships. Twenty (10 male) healthy participants (26.2 ± 4.0 years) underwent nine (following a familiarization run) randomized 10 min passive SAHC runs with RAP set above the head (P1), at the apex of the head (P2), or at heart level (P3) with foot‐level Gz at 1.0 g, 1.7 g and 2.4 g . Cerebral tissue saturation index (cTSI, cerebral perfusion surrogate), calf circumference (CC, central hypovolaemia), heart rate (HR) and digital heart‐level mean arterial blood pressure (MAP) were continuously recorded, in addition to incidence of pre‐syncopal symptoms (PSS). ΔCC and ΔHR increases were attenuated from P1 to P3 (ΔCC: 5.46 ± 0.54 mm to 2.23 ± 0.42 mm; ΔHR: 50 ± 4 bpm to 8 ± 2 bpm, P < 0.05). In addition, ΔcTSI decrements were also attenuated (ΔcTSI: −2.85 ± 0.48% to −0.95 ± 0.34%, P < 0.05) and PSS incidence lower in P3 than P1 ( P < 0.05). A positive linear relationship was observed between ΔCC and ΔHR with increasing +Gz, and a negative relationship between ΔCC and ΔcTSI, both independent of RAP. Our data suggest that movement of RAP towards the heart (reduced g‐gradient), independent of foot‐level Gz, leads to improved g‐tolerance. Further investigations are required to assess the effect of differential baroreceptor feedback (i.e. aortic–carotid g‐gradient). Key points: The aim of this study was to determine the effect of rotational axis position (RAP and thus g‐gradient) during short‐arm human centrifugation (SAHC) upon cardiovascular responses, cerebral perfusion and g‐tolerance. In 10 male and 10 female participants, 10 min passive SAHC runs were performed with the RAP above the head (P1), at the apex of the head (P2), or at heart level (P3), with foot‐level Gz at 1.0 g, 1.7 g and 2.4 g . We hypothesized that movement of the RAP from above the head (the conventional position) towards the heart might reduce central hypovolaemia, limit cardiovascular responses, aid cerebral perfusion, and thus promote g‐tolerance. Moving the RAP footward towards the heart decreased the cerebral tissue saturation index, calf circumference and heart rate responses to SAHC, thereby promoting g‐tolerance. Our results also suggest that RAP, and thus g‐gradient, warrants further investigation as it may support use as a holistic spaceflight countermeasure.